Coated cutting tool

By forming a specific composition of Al and Ti nitride hard film on the cutting tool, the problem of insufficient durability of nitride films in the prior art is solved, and higher heat resistance and wear resistance are achieved, which is suitable for high Processing of hardness steel.

CN119278107APending Publication Date: 2025-01-07MOLDINO TOOL ENG LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202380042994.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-06-27
Filing Date
2023-06-23
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

The existing nitride film-covering cutting tools with Al and Ti as main body still have room for improvement in durability, especially in the processing of high-hardness steel, which is prone to film peeling and tool damage.

Method used

A nitride hard film containing 60-70 atomic % Al, 20-40 atomic % Ti and 1-10 atomic % W, Cr, Ta, Nb, Zr, Mo, V and other elements was used, and sputtering The film with a face-centered cubic lattice structure is formed, and the half-maximum width of the X-ray diffraction peak on the (111) surface is between 0.75° and 0.95°, avoiding the occurrence of a tightly arranged hexagonal fill structure, increasing the heat resistance of the film and Abrasion resistance.

Benefits of technology

It significantly improves the durability and wear resistance of the cladding cutting tool, reduces film damage and tool wear, and maintains excellent performance in the processing of high-hardness steel.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119278107A_ABST
    Figure CN119278107A_ABST
Patent Text Reader

Abstract

A coated cutting tool according to an embodiment is provided with a base material and a hard coating film formed on the base material. The hard coating film is a nitride containing 60-70 at% of Al, 20-40 at% of Ti, and 1-10 at% of one or more elements selected from the group consisting of W, Cr, Ta, Nb, Zr, Mo, and V with respect to the total amount of metal (including semimetal) elements, nitrogen element, and Ar element, with respect to the total amount of the metal (including semimetal) elements, nitrogen element, and Ar element, the content of the nitrogen element being less than or equal to 1 at%, and the content of the Ta element being less than or equal to 1 at%, with respect to the total amount of the metal (including semimetal) elements, the nitrogen element, and the Ar element being less than or equal to 1 at%. Ar is contained in an amount of from 0.01 at% to 0.15 at% (inclusive). The crystal structure of the hard coating film is a face-centered cubic lattice structure, and the half-width of the X-ray diffraction peak of the (111) plane of the hard coating film is 0.75-0.95 DEG (inclusive).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to covered cutting tools.

[0002] This application claims priority based on patent application No. 2022-102962 filed in Japan on June 27, 2022, and the contents are incorporated herein by reference. Background Art

[0003] In the past, as a technology for improving the life of cutting tools, a surface treatment technology in which a hard film composed of various ceramics is coated on the surface of the cutting tool is used. Among the hard films, nitride films of aluminum (Al) and titanium (Ti) are widely used due to their excellent wear resistance and heat resistance. In addition, nitride films containing other metal elements mainly composed of Al and Ti have also been proposed. For example, cited document 1 discloses a coated cutting tool provided with an AlTiW nitride film containing tungsten (W) element.

[0004] Patent Document 1: International Publication No. 2014 / 157688

[0005] According to the research conducted by the present inventors, it has been confirmed that there is room for improvement in the durability of the conventionally proposed coated cutting tool provided with a nitride film mainly composed of Al and Ti. Summary of the invention

[0006] One embodiment of the present invention is a coated cutting tool comprising a substrate and a hard film formed on the substrate.

[0007] The hard film is a nitride, wherein the nitride contains 60 atomic % to 70 atomic % of Al, 20 atomic % to 40 atomic % of Ti, 1 atomic % to 10 atomic % of one or more selected from W, Cr, Ta, Nb, Zr, Mo and V, relative to the total amount of metal (including semi-metal) elements, and contains 0.01 atomic % to 0.15 atomic % of Ar, relative to the total amount of metal (including semi-metal) elements, nitrogen elements and Ar elements.

[0008] The crystal structure of the hard film is a face-centered cubic lattice structure, and the half-value width of an X-ray diffraction peak of the (111) plane of the hard film is 0.75° or more and 0.95° or less.

[0009] The half-value width of the X-ray diffraction peak of the (111) plane of the hard film is preferably 0.78° or more and 0.95° or less.

[0010] The hard film preferably does not have a diffraction peak intensity corresponding to AlN having a hexagonal close-packed structure in an intensity distribution of a selected area electron diffraction pattern obtained using a transmission electron microscope.

[0011] According to the present invention, a coated cutting tool having excellent durability can be provided. BRIEF DESCRIPTION OF THE DRAWINGS

[0012] Figure 1 This is an example of a cross-sectional observation photograph (×10,000 times) of the hard film according to Example 1.

[0013] Figure 2 This is an example of a cross-sectional observation photograph (×10,000 times) of the hard film according to Example 2.

[0014] Figure 3 This is an example of a cross-sectional observation photograph (×10,000 times) of the hard film according to Comparative Example 1. DETAILED DESCRIPTION

[0015] The coated cutting tool of this embodiment has a substrate and a hard film formed on the substrate. The hard film involved in this embodiment is a nitride mainly composed of Al and Ti, and the nitride is a film type with excellent heat resistance and wear resistance. If necessary, an intermediate film can also be provided between the substrate and the hard film. In addition, if necessary, an upper layer can also be provided on the hard film. The following is a detailed description.

[0016] In the coated cutting tool of the present embodiment, the substrate is not particularly limited, but a WC—Co based cemented carbide having excellent strength and toughness is preferably used as the substrate.

[0017] Al

[0018] Regarding the hard film involved in the present embodiment, Al is 60 atomic % or more and 70 atomic % or less relative to the total amount of metal (including semi-metal. The same applies hereinafter) elements. Al is an element that improves the heat resistance of the hard film. By increasing the Al content of the hard film, the heat resistance of the hard film is improved. In addition, by increasing the Al content of the hard film, it is easy to form an oxidation protection film on the surface of the tool, and it is easy to suppress film damage. In addition, by increasing the Al content of the hard film, the film structure becomes fine, and it is easy to suppress film damage. In order to give full play to these Al addition effects, regarding the hard film involved in the present embodiment, Al is 60 atomic % or more relative to the total amount of metal elements. Preferably, the Al of the hard film involved in the present embodiment is 62 atomic % or more.

[0019] On the other hand, when the Al content of the hard film is too much, the AlN of the fragile hexagonal close-packed structure (hereinafter referred to as hcp structure) increases, reducing the durability of the coated cutting tool. Therefore, with respect to the hard film involved in this embodiment, Al is 70 atomic % or less relative to the total amount of metal elements. Preferably, the Al of the hard film involved in this embodiment is 68 atomic % or less. More preferably, the Al of the hard film involved in this embodiment is 65 atomic % or less.

[0020] Ti

[0021] In the hard film according to the present embodiment, Ti is 20 atomic % or more and 40 atomic % or less relative to the total amount of metal elements. In the hard film according to the present embodiment, Ti is 20 atomic % or more relative to the total amount of metal elements, so that the crystal structure of the hard film becomes a face-centered cubic lattice structure, and the durability of the coated cutting tool is improved. In addition, in the hard film according to the present embodiment, Ti is 40 atomic % or less relative to the total amount of metal elements, so that the heat resistance of the hard film is improved.

[0022] 《One or more selected from W, Cr, Ta, Nb, Zr, Mo and V》

[0023] With respect to the hard film involved in the present embodiment, one or more selected from W, Cr, Ta, Nb, Zr, Mo and V is 1 atomic % or more and 10 atomic % or less relative to the total amount of metal elements. These elements are transition metal elements belonging to the 4a group, 5a group and 6a group in the periodic table, and are usually added to AlTi nitride in order to improve the film properties such as heat resistance, wear resistance and lubricity. In order to fully obtain the effect of improving the film properties by adding these elements, with respect to the hard film involved in the present embodiment, one or more selected from W, Cr, Ta, Nb, Zr, Mo and V is set to 1 atomic % or more relative to the total amount of metal elements. It is further preferably set to 2 atomic % or more. It is further preferably set to 3 atomic % or more. On the other hand, when the addition amount of elements other than Al and Ti is too much, the film properties of the hard film are sometimes reduced. Therefore, with respect to the hard film involved in the present embodiment, one or more selected from W, Cr, Ta, Nb, Zr, Mo and V is set to 10 atomic % or less relative to the total amount of metal elements. Furthermore, it is preferably set to 8 atomic % or less. It is further preferably set to 6 atomic % or less. In particular, by applying a hard film added with W in the cutting of high-hardness steel, there is a tendency that the durability of the coated cutting tool is excellent, so it is preferred.

[0024] Ar

[0025] The hard film involved in the present embodiment contains 0.01 atomic % or more and 0.15 atomic % or less of Ar relative to the total amount of metal (including semi-metal) elements, nitrogen elements and Ar elements (the whole hard film). The hard film involved in the present embodiment is a hard film formed by sputtering. The hard film of the present embodiment is a sputtering film, and is a sputtering hard film. The hard film formed by the sputtering method has compressive residual stress and few particles (ドロップレット), and becomes a smoother surface state than the hard film formed by the arc ion plating method. In addition, since in the sputtering method, Ar ions are used to sputter the target component to coat the hard film, Ar is contained in the formed hard film. The hard film involved in the present embodiment contains 0.01 atomic % or more of Ar relative to the total amount of metal (including semi-metal) elements, nitrogen elements and Ar elements (the whole hard film). In order to stabilize the coating process, the Ar content of the hard film according to the present embodiment is preferably set to 0.03 atomic % or more.

[0026] When the crystal grain size of the hard film is micronized, the hardness is increased. On the other hand, the grain boundaries become more numerous, and the Ar contained in the hard film is enriched at the grain boundaries. When the Ar content of the hard film is high, the toughness of the hard film is reduced, and it is difficult to fully exert the tool performance. In order to reduce the Ar enriched at the grain boundaries of the hard film, the Ar of the hard film involved in this embodiment is set to 0.15 atomic % or less. Preferably, the Ar of the hard film involved in this embodiment is set to 0.10 atomic % or less.

[0027] Crystal Structure

[0028] The hard film involved in this embodiment is a face-centered cubic lattice structure (fcc structure). In this embodiment, the so-called face-centered cubic lattice structure means that in the X-ray diffraction of the hard film, there is only a diffraction peak intensity corresponding to the face-centered cubic lattice structure. That is, in the hard film of this embodiment, no diffraction peak corresponding to the hcp structure and the bcc structure is observed in the X-ray diffraction. In the X-ray diffraction, the hard film having the diffraction peak intensity corresponding to AlN of the hcp structure reduces the durability of the coated cutting tool.

[0029] In the hard film according to the present embodiment, the diffraction peak intensity of the (200) plane or (111) plane of the face-centered cubic lattice structure is the maximum intensity among the diffraction peak intensities of the multiple diffraction peaks observed in X-ray diffraction. In the hard film according to the present embodiment, it is preferred that the diffraction peak intensity of the (111) plane is the maximum intensity in X-ray diffraction. By making the diffraction peak intensity of the (111) plane the maximum intensity, the columnar structure of the hard film is easily finer.

[0030] The hard film involved in the present embodiment preferably does not have a diffraction peak intensity corresponding to AlN with an hcp structure in the intensity distribution of the selected area electron diffraction pattern using a transmission electron microscope. Even if there is no diffraction peak intensity corresponding to AlN with an hcp structure in X-ray diffraction, there is sometimes a diffraction peak intensity corresponding to AlN with an hcp structure in the intensity distribution of the selected area electron diffraction pattern using a transmission electron microscope. By not having a diffraction peak intensity corresponding to AlN with an hcp structure in the intensity distribution of the selected area electron diffraction pattern using a transmission electron microscope, the amount of AlN with an hcp structure contained in the microstructure is reduced, and the durability of the coated cutting tool can be further improved.

[0031] Half-width

[0032] It is important that the film structure of the hard film involved in the present embodiment is fine. The fine film structure makes it easy to suppress tool damage during the processing of high-hardness steel. The inventors have confirmed that in the hard film as a face-centered cubic lattice structure, the half-peak width of the X-ray diffraction peak of the (111) plane, which is the densest plane, has a certain correlation with the size of the columnar particles of the film structure. In addition, it has been confirmed that by making the half-peak width (FWHM: full width at half maximum) of the X-ray diffraction peak of the (111) plane greater than 0.75° within the above-mentioned composition range, the columnar particles of the hard film become fine, and the durability of the coated cutting tool is also excellent. Preferably, the half-peak width of the X-ray diffraction peak of the (111) plane of the hard film involved in the present embodiment is greater than 0.78°. It is further preferred that the half-peak width of the X-ray diffraction peak of the (111) plane of the hard film involved in the present embodiment is greater than 0.80°. On the other hand, when the half-peak width value is too large, the film structure becomes amorphous, and the AlN of the hcp structure tends to increase. Therefore, the half-peak width of the X-ray diffraction peak of the (111) plane of the hard film involved in the present embodiment is 0.95° or less. Preferably, the half-peak width of the X-ray diffraction peak of the (111) plane of the hard film involved in the present embodiment is 0.92° or less. It is further preferred that the half-peak width of the X-ray diffraction peak of the (111) plane of the hard film involved in the present embodiment is 0.88° or less.

[0033] The half-value width of the X-ray diffraction peak of the (200) plane of the hard film of the present invention is preferably 0.90° or more and 1.1° or less. This makes it easy to obtain a hard film having a face-centered cubic lattice structure of a fine structure.

[0034] The half-value width of the X-ray diffraction peak can be determined using an X-ray diffraction apparatus under the measurement conditions of a tube voltage of 45 kV, a tube current of 40 mA, an X-ray source of Cukα (λ=0.15405 nm), and a 2θ range of 20 to 80 degrees.

[0035] The hard film involved in this embodiment may contain other metal elements or semi-metal elements within the range of satisfying the above composition and half-peak width. For example, it may contain one or more metal elements or semi-metal elements selected from Si, B, Cu, Y and Yb. When containing these elements, it is preferably 1 atomic % or more and 5 atomic % or less.

[0036] 《Intermediate membrane》

[0037] The coated cutting tool of this embodiment may be provided with an intermediate film between the substrate and the hard film as required. For example, a nitride, carbonitride, or carbide containing one or more elements selected from Ti, Cr, and Al may be provided. The coated cutting tool of this embodiment may be provided with a hard film directly above the substrate.

[0038] "upper layer"

[0039] The coated cutting tool of this embodiment may be provided with an upper layer having a different component ratio or other composition from the hard film of this embodiment as required on the hard film of this embodiment. The upper layer may be a plurality of layers or a laminated film.

[0040] In the coating of the hard film involved in this embodiment, it is preferred to also apply a sputtering method in which power is applied to the targets sequentially. When switching the targets to which power is applied, a time is set for simultaneously applying power to the target to which power application ends and the target to which power application starts.

[0041] When the time for simultaneously applying power to the alloy target at the end of power application and the alloy target at the beginning of power application is too short or too long, the target is not ionized sufficiently, and it is difficult to form sufficient nitrides in the hard film. Therefore, it is preferred that the time for simultaneously applying power to the alloy target at the end of power application and the alloy target at the beginning of power application be set to be greater than 1 microsecond and less than 20 microseconds. The maximum power density of the power pulse is preferably 0.5 kW / cm 2 In order to increase the ionization rate of the target component, it is preferable to use three or more AlTiMe alloy targets (Me is one or more selected from W, Cr, Ta, Nb, Zr, Mo and V).

[0042] In order to make the hard film have a face-centered cubic lattice structure and form a fine-grained structure with high crystallinity, the film formation temperature is preferably set to 400°C to 460°C, and the negative bias voltage applied to the cutting tool as a substrate is controlled within the range of -70V to -40V.

[0043] Hereinafter, the present invention will be described in more detail with reference to Examples and Comparative Examples, but the present invention is not limited to the following Examples.

[0044] Example 1

[0045] <Tools>

[0046] As a tool serving as a substrate, a double-edged ball-end mill made of cemented carbide (tool diameter 1.0 mm, manufactured by MOLDINO Co., Ltd.) having a composition of WC (bal.)-Co (8.0 mass%)-Ta (0.3 mass%), an average WC grain size of 0.5 μm, and a hardness of 93.2 HRA (Rockwell hardness, value measured in accordance with JIS G 0202) was prepared.

[0047] A sputtering device capable of carrying 12 sputtering evaporation sources was used. Among these evaporation sources, six AlTiW alloy targets were set in the device as evaporation sources. In addition, the target size used was 16 cm in diameter and 12 mm in thickness.

[0048] The tool was fixed on the sample holder in the sputtering device, and a bias power supply was connected to the tool. In addition, the bias power supply was a structure that applied a negative bias voltage to the tool independently of the target. The tool rotated at three revolutions per minute and revolved through the fixing fixture and the sample holder. The distance between the tool and the target surface was set to 100 mm.

[0049] Ar and N2 were used as the introduced gas, and the introduced gas was introduced from a gas supply port provided in the sputtering device.

[0050] <Bombardment treatment>

[0051] First, before coating the tool with a hard film, the tool is bombarded in the following order. The sputtering device is evacuated, and then heated for 30 minutes at a furnace temperature of 430°C by a heater in the sputtering device. Then, Ar gas is introduced into the furnace of the sputtering device. Then, a DC bias voltage is applied to the tool, and the tool is cleaned (bombarded) with Ar ions.

[0052] Next, Ar gas and nitrogen gas were introduced into the furnace of the sputtering device to adjust the pressure in the furnace. A DC bias voltage was applied to the tool and a 0.8 kW / cm 2 The maximum power density was set so that the discharge time of each power cycle was 0.8 milliseconds and the time for applying power to the AlTiW alloy target was 4 microseconds. Then, power was continuously applied to each alloy target to form a hard film with a total film thickness of about 3 μm. The details of the film forming conditions are shown in Table 1.

[0053] [Table 1]

[0054]

[0055] The hardness and elastic modulus of the hard film were measured using a nanoindentation tester (ENT-2100 manufactured by ELIONIX INC).

[0056] The determination was performed using an X-ray diffraction apparatus (EMPYREAN manufactured by PaNalytical Co., Ltd.) under the following measurement conditions: tube voltage 45 kV, tube current 40 mA, X-ray source Cukα (λ=0.15405 nm), and 2θ of 20 to 80 degrees.

[0057] The film composition of the hard film was measured using a wavelength dispersive electron probe microanalyzer (WDS-EPMA) attached to an electron probe microanalyzer (JXA-8500F manufactured by JEOL Ltd.). The measurement conditions were an acceleration voltage of 10 kV and an irradiation current of 5 × 10 -8 A, introduction time 10 seconds, within the analysis area of ​​1 μm diameter range of five points measured, according to the average value of the metal content ratio of the hard film and Ar relative to the total content of metal elements, nitrogen elements and Ar elements. The results of the physical property evaluation are shown in Table 2.

[0058] [Table 2]

[0059]

[0060] 《Cutting conditions》

[0061] The produced coated cutting tools were subjected to dry cutting tests and wet cutting tests under the cutting conditions shown below. The cutting test results are shown in Table 3. The details of the cutting conditions are as follows.

[0062] <Processing conditions>

[0063] Cutting method: bottom cutting

[0064] Workpiece: STAVAX (52HRC)

[0065] Tool used: Double-edged ball end mill (tool diameter 1.0mm, neck length 6mm)

[0066] Cutting depth: axial 0.04mm, radial 0.04mm

[0067] Cutting speed: 75m / min

[0068] Single-edge feed rate: 0.018mm / edge

[0069] Cutting distance: Dry type = 60m, Wet type = 40m

[0070] Wet machining is carried out by pouring water-soluble cutting oil diluted to a concentration of about 10% directly onto the part of the workpiece to be machined by the tool through a cooling hose.

[0071] [Table 3]

[0072]

[0073] The comparative examples including the hcp structure in the crystal structure all experienced film peeling in the wet cutting test at an early stage and could not continue processing. During cutting, very high cutting heat is generated at the contact part between the tool and the workpiece. Tool damage called thermal cracks often occurs due to the expansion and contraction of the tool caused by the cutting heat. This is more significant in wet processing with a high cooling effect. Therefore, in wet processing, the comparative examples including the fragile hcp structure are presumed to have film peeling at an early stage.

[0074] In Comparative Example 8, the absolute value of the negative bias voltage applied to the substrate during the coating of the hard film was large, and excessive residual compressive stress was applied to the hard film, resulting in early film peeling in the dry cutting test.

[0075] In addition, although Comparative Example 1, which does not include an hcp structure in the crystal structure, did not cause early film peeling in the wet cutting test, the maximum wear width became larger because the film structure was slightly larger than that of the present embodiment.

[0076] On the other hand, this example showed excellent durability in both the wet cutting test and the dry cutting test. In particular, Example 1, which had a finer hard film, had a smaller maximum wear width and excellent wear resistance in all cutting tests, and was a coated cutting tool with excellent durability.

Claims

1. A coated cutting tool, characterized in that: A substrate and a hard film formed on the substrate. The hard film is a nitride, wherein the nitride contains 60 atomic % to 70 atomic % of Al, 20 atomic % to 40 atomic % of Ti, 1 atomic % to 10 atomic % of one or more selected from W, Cr, Ta, Nb, Zr, Mo and V, relative to the total amount of metal elements including semi-metals, nitrogen elements and Ar elements, and contains 0.01 atomic % to 0.15 atomic % of Ar, The crystal structure of the hard film is a face-centered cubic lattice structure, and the half-value width of an X-ray diffraction peak of the (111) plane of the hard film is 0.75° or more and 0.95° or less.

2. The coated cutting tool according to claim 1, characterized in that: The half-value width of the X-ray diffraction peak of the (111) plane of the hard film is 0.78° or more and 0.95° or less.

3. The coated cutting tool according to claim 1 or 2, characterized in that: The hard film does not have a diffraction peak intensity corresponding to AlN having a hexagonal close-packed structure in the intensity distribution of a selected area electron diffraction pattern obtained using a transmission electron microscope.

Citation Information

Patent Citations

  • Method for producing dry flower, method for producing dry plant, method for producing food, and method for producing dry leaf

    JP2022102962A

  • Coated cutting tool

    CN110691662A

  • Coated cutting tool, and manufacturing method and chemical vapor deposition device for same

    CN111032259A

  • Hard film for cutting tools, cutting tool coated with hard film, process for forming hard film, and target used to form hard film

    US20020168552A1

  • Coated cutting tool

    US20200198017A1